Pengaruh lama perendaman dalam larutan kapur dan asam sitrat pada pembuatan gelatin untuk marshmallow dari tulang ikan tenggiri (Scomberomorus commersoni) - Yazid Ismi Intara; Deddy Muladi Togatorop; Bosman Sidebang Sidebang (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Mackerel is a type of bony fish that contains which can be converted into gelatin by extracting it with an acid solution. This study aims to obtain the physical and chemical characteristics of gelatin from mackerel bone extract, physical characteristics of the marshmallow made from mackerel gelatin, and organoleptic test results on the product marshmallow from mackerel gelatin. The design in this study used a Completely Randomized Design (CRD) with one different factor, namely lime soaking time for 24 hours (K1) and 48 hours (K2) and 6% citric acid immersion for 12 hours (S1), 18 hours (S2) and 24 hours (S3). The test results for the water content of gelatin from mackerel bone waste were 6-16.33%, the ash content was 0.34-0.56%, and the ranged from 1.16-3.8%. Marshmallow moisture content ranged from 11.66 to 14.66 %, and the texture/hardness was 80 - 92.1 mm/g/s. The results of the hedonic test showed that the level of panelists preference the taste of the product marshmallow ranges from 2.1 - 3.3 (dislikes-neutral), on texture has a scale of 2.6 - 3.4 (dislikes - neutral), on aroma ranged from 1.9 - 3.6 (immensely dislike - neutral), on color between 2.5 - 3.7 (dislike - neutral) and overall (appearance) between 2.4 - 3.3 (dislike - neutral).